2011
DOI: 10.1130/g32153.1
|View full text |Cite
|
Sign up to set email alerts
|

Geological record of ice shelf break-up and grounding line retreat, Pine Island Bay, West Antarctica

Abstract: The catastrophic break-ups of the fl oating Larsen A and B ice shelves (Antarctica) in 1995 and 2002 and associated acceleration of glaciers that fl owed into these ice shelves were among the most dramatic glaciological events observed in historical time. This raises a question about the larger West Antarctic ice shelves. Do these shelves, with their much greater glacial discharge, have a history of collapse? Here we describe features from the seafl oor in Pine Island Bay, West Antarctica, which we interpret a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 28 publications
8
148
3
Order By: Relevance
“…According to Larter et al (in press) the rates of change currently observed in the ASE are too high to be a simple continuation of deglaciation from the LGM as such high modern retreat rates (i.e., 0.95 ± 0.09 km yr -1 between 1992-2011; Park et al 2013) would have resulted in deglaciation of the entire continental shelf within 500 years, which is in conflict with recent marine geological data (e.g., Smith et al, 2011). There is also a growing body of geomorphological evidence that ice sheet retreat following the LGM was oscillatory with periods of rapid change punctuated by periods of relative stability (Graham et al, 2010;Jakobsson et al 2011). …”
Section: Introductioncontrasting
confidence: 38%
See 2 more Smart Citations
“…According to Larter et al (in press) the rates of change currently observed in the ASE are too high to be a simple continuation of deglaciation from the LGM as such high modern retreat rates (i.e., 0.95 ± 0.09 km yr -1 between 1992-2011; Park et al 2013) would have resulted in deglaciation of the entire continental shelf within 500 years, which is in conflict with recent marine geological data (e.g., Smith et al, 2011). There is also a growing body of geomorphological evidence that ice sheet retreat following the LGM was oscillatory with periods of rapid change punctuated by periods of relative stability (Graham et al, 2010;Jakobsson et al 2011). …”
Section: Introductioncontrasting
confidence: 38%
“…6) does raise questions about the deglacial model published in Kirshner et al (2012). Furthermore, if the Jakobsson et al (2011) model for formation of corrugations is also correct, then the ridges imaged on GZW4 must have formed before GZW5, otherwise it would have been impossible to generate icebergs with deep enough keels to form them (see Fig. 4 in Jakobsson et al, 2012).…”
Section: Larter Et Al (In Press) Raised the Issue That If The Kirshmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar corrugations have been mapped beneath the Pine Island Glacier ice shelf and within iceberg scours located in the main PIT. These corrugations are believed to originate from tidally-modulated, periodic keel grounding beneath a seaward-flowing ice shelf or at the trailing keel of tabular icebergs (Jakobsson et al, 2011). Jakobsson et al (2011) and Larter et al (2012) suggested that icebergs eroding linear, parallel scours may have been embedded within a mélange of sea and brash ice restricting iceberg movement and thus contributed to the linear orientation of the resulting scours as seen here.…”
Section: Linear Iceberg/ice Shelf Scoursmentioning
confidence: 92%
“…Does this reflect drainage of meltwater through pore spaces in the till by Darcian throughflow, or does it reflect the fact that existing multi-beam systems are, as yet, unable to resolve these kinds of features over the soft bed? These are unanswered questions, but ones which marine science has the potential to answer through acquisition of well-dated core chronologies and increasing improvements in multi-beam systems [124].…”
Section: (B) Investigations Of Ice-sheet History and Glacial Processementioning
confidence: 99%